Baseline results from the new EU27 EUROMOD (2007-2010) - Holguer Xavier Jara; Holly Sutherland; Silivia Avram; Paola De Agostini; Francesco Figari; Horacio Levy; Jekaterina Navicke; Alari Paulus; Olga Rastrigina; Iva Tasseva; Alberto Tumino (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper provides a description of the latest public release of EUROMOD (version F6.0++), a tax-benefit microsimulation model for the EU. First, we briefly report the process of constructing and updating EUROMOD. We then present indicators for income inequality and risk of poverty using EUROMOD and discuss the main reasons for differences between these and EU-SILC based indicators. We further compare EUROMOD indicators across countries and over time between 2007 and 2010. Finally, we provide estimates of marginal effective tax rates (METR) for all 27 EU countries in order to explore the effect of tax and benefit systems on work incentives at the intensive margin. Throughout we highlight both the potential of EUROMOD as a tool for policy analysis and the caveats that should be borne in mind when using it and interpreting results.
Keywords: C15; H24; H31; H55; I3; 330; microsimulation; redistribution; tax-benefit system; poverty; inequality; work incentives